On the fringe: tracking and evaluating changes in land use in the areas surrounding three national parks in Spain and Portugal - Prados, M. J. (2014)
Naturbanization analyses territorial changes in the surroundings of national parks brought about by the arrival of new settlers and economic activities, both of which are attracted by the value of the environment and landscape. This paper presents a comparison of the naturbanization processes in three national parks in Spain and Portugal (Doñana and Sierra Nevada National Parks, and Peneda-Gêres National Park, respectively) and in their areas of influence. Data is taken from Corine-Land Cover (1990-2006), which is the only available source of information about land use and land cover changes in the whole of the European Union. These changes have been interpreted and analysed using the Cross Tabulation Matrix developed by Pontius (2004). Land use changes connected to naturbanization processes are measured using Gains and Loss measurements. The intensification of changes in land use is one of the most significant developments associated with these processes, which have implications for the sustainable development and conservation of these areas.